Topological Study of Phase-Separated Ag-Conducting Chalcogenide Glasses Using Peak Force Quantitative Nano-Mechanical Characterization - Piarristeguy, Andrea A.; Le Parc, Rozenn; Ramonda, Michel; Escalier, Raphaël; Pradel, Annie (Frontiers in Materials, 2020)
Peak Force Quantitative Nano-Mechanical property mapping (PF-QNM) was used to explore the nanomechanical properties of binary GezSe100-z glasses and phase-separated Agx(Ge0.25Se0.75)100-x glasses. The indentation modulus decreases when the selenium content increases in the binary glasses and when the silver content increases in phase-separated ternary glasses as a consequence of the increasing flexibility of the network. At nanoscale level, PF-QNM measurements highlighted a higher indentation modulus for the Ag-rich phase than for the Ag-poor phase, together with a decrease of both local indentation moduli with the increase of silver content in the glass. A model to gain a further insight in the mean coordination numbers and compositions of the Ag-rich and Ag-poor phases, based upon the assumption of a decoupled effect of the variations in Ag and in Ge on the mechanical properties, is described in detail. In the framework of the model, the mean coordination numbers for the Ag-rich phase <NR> and Ag-poor phase < NP> keep on decreasing when the total silver content in the glasses increases. The Ge concentration differs in Ag-rich and Ag-poor phases. When the silver content in the glass increases, the Ge concentration decreases in both phases. The result, in turn, indicates that an increase in the conductivity of the Ag-rich phase when the total silver content increases, as shown previously by C-AFM, would not be only explained by an increase in silver content but also by a softening of the network and consequently by an increase of charge carrier mobility.